METHODOLOGICAL ASPECTS OF THE MORPHOLOGICAL DIVERSITY OF HAZELNUTS STUDYING ON THE EXAMPLE OF THE UKRAINIAN SELECTION CULTIVARS - Kolchanova О. V.; Los, S. A. (Forestry and Forest Melioration, 2018)
Introduction Morphological characteristics of plants’ cultivars and forms play an important role in creating descriptions, as well as in the identification of their differences. The detailed description of reproductive organs for most hazelnut cultivars of Ukrainian breeding has been compiled (Los 1992, Kosenko 2003, Kolchanova and Los 2014, Kolchanova 2018), but the morphological features of vegetative organs have not been studied in practice. Morphological differentiation of leaves may be an additional indicator for the differences or similarities of cultivars by phenotypic features. The aim of the study was to use in practice the method which help examine and identify hazelnut plants by morphological characteristics of the leaf and to test it on the example of hazelnuts cultivars of Ukrainian breeding. Materials and Methods We described the method meant to examine the morphological characteristics of leaf blades, as well as the results of the study of 12 hazelnuts cultivars of the URIFFM breeding (Fedor Pavlenko). Samples of leaves (4-10 pieces of each cultivar) were harvested on collection plantation on the territory of the arboretum of the Kharkiv National Agrarian University named after V. V. Dokuchayev. The leaf length, width, petiole length, and leaf area were measured in the ImageJ programme. For each leaflet plate and its separate morphological element (apex, base, teeth), the points were given according to the developed 5- point scale. Based on the scale, the average values for each cultivar were defined. We also used the S. A. Mamaev’s scale to define the variability of the morphological characteristics of leaf blades. Results The cultivars ’Serebrysty’, ’Borovsky’, ’Krasnolysty’, ’Olimpiysky’ and ’Veleten’ dominated by the parameters of length, width and area of leaf. The cultivars ’Lozovsky sharovidny’, ’Pirozhok’, ’Klinovidny’ and ’Kharkiv-4’ had relatively small leaves. The cultivars ’Borovsky’, ’Lozovsky sharovidny’’ and ’Serebristy’ had the most marked roundness of the leaf blade. The most elongated leaf blade was found in the cultivars ’Pirozhok’ and ’Klinovidny’. The cultivars ’Dokhodny’, ’Kharkiv-4’ and ’Veleten’ had the longest petiole. Correlation analysis showed positive moderate correlations between the length of the leaf and its petiole (r = 0.57), between the leaf shape and its area (r = 0.56), between the leaf width to length ratio and the shape of the teeth of the first order (r = 0.57). A paired comparison of all 12 cultivars according to 8 characteristics showed that the cultivars ’Klinovidny’ and ’Pirozhok’ had the highest degree of similarity in morphological features of all the components of the leaf blade. The ’Lozovsky sharovidny’ and ’Olimpiysky’, ’Olimpiysky’ and ’Serebristy’, and ’Serebristy’ and ’Veleten’ cultivars, on the contrary, differed in all characteristics. In general, distinctive features prevailed. According to the results of the cluster analysis, the cultivar ’Serebristy’ significantly differs from all the cultivars. The ’Lozovsky bulavovidny’ cultivar had a significant differentiation in all indicators. The most similar groups of cultivars were ’Borovsky’ – ’Prevoshodny’, ’Krasnolisty’–’Veleten’ and’ ’Klinovidny’–’Pirozhok’. As a result of the research, we worked out the detailed morphological description of the hazelnut cultivars of the URIFFM breeding (Fedor Pavlenko) by leaf morphological characteristics. Conclusions The leaves of the studied cultivars were described as small, relatively small, medium and large. The length of the leaf petiole of cultivars is more variable than its size. Moreover, there are the cultivars with elongated, rounded and wide-rounded leaves. We came to the conclusion that the degree of similarity and differences among the cultivars varies. The predominance of different features shows that the presented method meant to characterize and identify hazelnuts cultivars can be successfully applied. 5 Figs, 8 Tables, 14 Refs.